Fluid sloshing dynamic performance in a liquid hydrogen tank. (21st May 2019) - Liu, Zhan; Feng, Yuyang; Lei, Gang; Li, Yanzhong
Abstract: In the present study, a numerical model is built to investigate the hydrodynamic performance in a sloshing liquid hydrogen tank under a sinusoidal excitation. The motion mesh coupled the volume of fluid method is adopted to capture the fluctuation of the free surface during sloshing. The sloshing dynamic response of the free surface is specially evaluated. Meanwhile, the sloshing force and moment, and pressure variation are numerically studied. The results show that the free surface has stable interface shapes with "Z" or "S" type profiles in the initial period. As time elapses, the sinusoidal wave propagates, some disturbances occur at the interface with different wave amplitudes. For fluid close to the tank wall, it suffers much more from external excitation with large amplitude fluctuations. For the symmetrically distributed measuring points, opposite fluctuating profiles form with almost the same amplitude. Influenced by fluid motion, the point of the maximum liquid pressure makes fluctuations as well. The measuring points far from the symmetry axis of the tank have severe fluctuating variations. With some valuable conclusions arrived, the present study is significant to the in-depth comprehension on fluid sloshing dynamical behavior in non-isothermal cryogenic tanks. Highlights: A numerical model is established to investigate the sloshing hydrodynamic performance in a liquid hydrogen tank. The motion mesh coupled the VOF method is adopted to predict fluctuations of the free surface. The interface fluctuation elevation, sloshing force and moment and pressure change are numerically studied.